Halliwell's film guide - Halliwell, Leslie (New York Charles Scribner's Sons, 1985)
From the best known film buff of all comes the fifth edition of the best-selling Film Guide--incorporating an unprecedented amount of new material, including full information about the availability on video of over a thousand films.

There are four hundred additional entries covering films of 1983 and 1984 alone. And, as in the last edition, Halliwell has delved more deeply than ever before into a single decade. This time the thirties have been researched, to the extent of fifteen hundred more titles, and few people in the world will be able to name an English-speaking film from that era which is not how included.

Those new to the Film Guide will find it a mine of essential information about as many films as can be crammed within its covers. The new edition surpasses even the previous high standards of the guide that has brightly provided the answers to millions of movie questions the world over.
A gift of Marissa Yang Ricardo.
Keywords: Motion pictures -- Dictionaries